Knee arthritis in an HIV positive patient - not associated with antiretroviral therapy - I Nyoman Suarjana; Yoga I Kasjmir; Bambang Setiyohadi (Indonesian Rheumatology Association, 2009)
Human immunodefi ciency virus (HIV)-associated arthritis is an oligoarthritis which predominantly affect the knees and ankles. It tends to be selflimited and to last less than six weeks. However, some patients with HIV-associated arthritis have been reported to have a disease course of more than six weeks with joint destruction. Synovial fl uid cultures are typically sterile and radiographs of the affected joints are usually normal except in those rare patients with a prolonged duration of symptoms in whom joint-space narrowing can occur.1,2 The pathophysiology of HIV specific arthritis types is not fully understood but drugs of the highly active antiretroviral therapy, in particular indinavir, are supposed to cause arthritis or rheumatological complaints.3 However,recently both human T-lymphotropic virus (HTLV) type I and HTLV-II have been suggested to induce infl ammatory or autoimmune reactions which can increase signifi cantly the incidence of arthritis.4 We report a patient with HIV infection presenting as knee arthritis which was apparently not associated with antiretroviral therapy.